2016
DOI: 10.1227/neu.0000000000001056
|View full text |Cite
|
Sign up to set email alerts
|

A Phase III Clinical Trial Showing Limited Efficacy of Autologous Mesenchymal Stem Cell Therapy for Spinal Cord Injury

Abstract: Single MSCs application to intramedullary and intradural space is safe, but has a very weak therapeutic effect compared with multiple MSCs injection. Further clinical trials to enhance the effect of MSCs injection are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 58 publications
0
98
0
Order By: Relevance
“…However, performance of all lesioned animals plateaued 2 months after injury ( Figure 6E) and would not have been expected to improve spontaneously after month 12 (40). Moreover, human clinical trials would be designed to detect late, within-subjects improvement from a chronic, stable baseline score, as in this study, because patients typically show little or no improvement in function at chronic post-injury time points (41)(42)(43).…”
Section: Resultsmentioning
confidence: 98%
“…However, performance of all lesioned animals plateaued 2 months after injury ( Figure 6E) and would not have been expected to improve spontaneously after month 12 (40). Moreover, human clinical trials would be designed to detect late, within-subjects improvement from a chronic, stable baseline score, as in this study, because patients typically show little or no improvement in function at chronic post-injury time points (41)(42)(43).…”
Section: Resultsmentioning
confidence: 98%
“…Although treatment with MSCs has been previously shown to exert positive effects in rodent models of SCI (Alexanian et al., 2011, Nakajima et al., 2012), their prolonged therapeutic effects and success in human clinical trials have been limited (Oh et al., 2016, Park et al., 2012). Genetic modification of MSCs, for example by overexpression of neurotrophic or growth factors, can further enhance their well-known beneficial effects and improve therapeutic outcome following CNS trauma (reviewed in Cui et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no clinical improvement of the neurological function had occurred at the end of this study [85]. Similarly, there are also data indicating that there is no significant improvement in Basso, Beattie, and Bresnahan (BBB) score after MSC transplantation for SCI [86, 87]. Pal et al reported that there is no effectiveness of the treatment involved after MSC injection for a of total 20 SCI patients during 1–3 years follow-up [88].…”
Section: Function Of Msc Transplantation After Scimentioning
confidence: 99%